Connecting Myself to Indian Residential Schools and the Sixties Scoop - Salazar, Alexa; Crowe-Salazar, Noela (First Peoples Child & Family Review, 2020)
This is a joint work between my Mom and I. It begins with a story passed down to my Mom about my grandfather’s experience at an Indian Residential School. My Mom asks me questions about the story and I respond, learning more as we talk. We ended up writing back and forth to one another over a few days to complete this. I found it very emotional and hard to talk about.We share this story fully acknowledging it is only one story, and it is shared with the intent for learning. I have heard many people say Residential Schools happened a long time ago. My mom started to share this story several years ago with primarily non-Indigenous social work students to demonstrate how Residential School and the Sixties Scoop impacted the five generations she speaks of in the story. My brother’s first day of school became a much bigger moment for her and my Mushum.We share this story with deep respect for all the families who were impacted by Residential Schools and the Sixties Scoop. We stand with you and support all of your voices and recognize many of you have lost far more than we have. For all our non-Indigenous family and friends, we share this with respect for you as well, and to foster better understanding and as a step towards reconciliation. This is our truth.